PERILAKU KONSUMEN DALAM PERSPEKTIF EKONOMI ISLAM - Suharyono Suharyono (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Human Resources in everyday life will never be separated by the fulfillment of needs or consumption. Islamic economics provides a picture and guidance in terms of consumption is justified and required in Islamic teachings that are guided by the rules of Shari'a. An item or commodity which is actually allowed to be used or consumed can be something that can be contrary to sharia depending on the behavior in using the goods or commodities. It can be concluded that consumption in Islam is loaded with spiritual values that indirectly lead consumers to avoid consumptive and keep the benefit is not just pleasure and satisfaction.